Review on the Studies and Advances of Machine Learning Approaches - Yongqing Wang; Qingxiu Li (Institute of Advanced Engineering and Science, 2014)
Artificial intelligence is a frontier field of computer science, and achieved considerable progress in the past few decades. Being an important research branch of artificial intelligence, machine learning has been successfully applied to many fields in recent years, such as expert system, automatic reasoning, natural language processing, pattern recognition, computer vision, intelligent robots, and so on. This article comprehensively introduces the main strategies of machine learning, and summarizes the existing problems and challenges. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3635